Antibiotic-induced dysbiosis of the rat oral and gut microbiota and resistance to Salmonella. (June 2020) - Wu, Hongle; Ma, Yue; Peng, Xian; Qiu, Wei; Kong, Lixin; Ren, Biao; Li, Mingyun; Cheng, Guo; Zhou, Xuedong; Cheng, Lei
Highlights: The gut microbiota underwent dramatic changes after both vancomycin and ampicillin treatment and could incompletely recover four weeks later. Oral microbiota did not show significant alterations in both alpha and beta diversity due to the use of antibiotics. Rats showed a decrease in colonization resistance in gut after antibiotics treatment for the first four days after infection. Abstract: Objectives: Antibiotics play a great role in the treatment of infectious diseases, but meantime, they cause great disturbances to host microbiota. Studies on different antibiotic-induced changes in host microbiota are relatively scarce. This study aimed to investigate the changes in oral and gut microbiota and possible alterations of gut resistance to Salmonella induced by the administration of antibiotics. Methods: The experiment was conducted by administering antibiotics to rats and detecting oral and gut microbiota by 16S rRNA gene sequencing. In second part, after treating with antibiotics or Lactobacillus rhamnosus the rats were infected by Salmonella Typhimurium and the pathogen burden in the gut was counted by colony forming unit assay. Results: The gut microbiota underwent dramatic changes after both vancomycin and ampicillin treatment. The alpha diversity sharply decreased, and the microbiota composition showed a significant difference. However, the gut microbiota recovered within four weeks after stopping antibiotics administration, although this recovery was incomplete. Oral microbiota did not show significant alterations in both alpha and beta diversities. The number of pathogens in the gut in the control group was significantly lower than that in the antibiotic-treated group but only lasted for the first 4 days after infection. Conclusions: Antibiotics cause dramatic alterations in the number and diversity of gut microbiota but not oral microbiota. These changes in the gut microbiota could incompletely recover four weeks later. When infected with pathogens after antibiotic administration, the rats show a decrease in colonization resistance in the gut for the first four days after infection.